Improvement of vertigo symptoms after 2 months of Vertigoheel treatment: a case series in patients with bilateral vestibulopathy and functional dizziness - Ganeva, Dilyana; Tiemann, Rolf; Duller, Stephan; Strupp, Michael (Frontiers in Neurology, 2023)
Background: Dizziness is a common leading symptom in bilateral vestibulopathy (BVP) and functional dizziness (FD) with significant negative effects on functional ability and quality of life. Vertigoheel is a widely used non-prescription drug for the treatment of vertigo. In order to generate systematic data for Vertigoheel in BVP and FD we conducted a non-interventional study assessing vertigo symptoms.Methods: This study was conducted as an open-label, prospective, monocentric, non-interventional case series (ClinicalTrials.gov identifier NCT05897853). Patients with BVP and FD received Vertigoheel according to market approval for an observational period of two months. Change from baseline after two months was assessed for the following endpoints: Dizziness Handicap Inventory (DHI) as the primary endpoint, quality of life (QoL) by EQ-5D-5L, and body sway by static posturography. Patients with FD were additionally assessed for depression and anxiety by PHQ-9 and GAD-7 questionnaires. Patients with BVP were assessed for vestibular function by video head impulse testing and caloric testing. Adverse events and other safety-related observations were evaluated.Results: Of 41 patients with FD and 13 with BVP, two with FD and none with BVP dropped out before the follow-up visit. Both patient groups showed a significantly ameliorated disability resulting from dizziness after two months: In BVP, the DHI decreased on average by 13.2 points from 45.4 to 32.2 (p<0.001). In FD, the DHI decreased on average by 12.0 points from 46.5 to 34.5 (p<0.001). In patients with FD, significant improvements were also observed for the secondary efficacy endpoints QoL, anxiety and depression. No significant change was observed for posturography readouts. In patients with BVP, there was no statistically significant improvements for the secondary endpoints QoL, posturography or vestibular function, within the observation period. The study found no evidence of a safety risk. This is a provisional file, not the final typeset articleThe study provides evidence for Vertigoheel's clinical safety and limited evidencebecause of the non-interventional designfor its effectiveness in BVP and FD that are considered as disease entities with high medical need for new treatment options. The results may serve as the basis for randomized placebo-controlled trials.